Development of in-situ bismuth film electrode for differential pulse anodic stripping voltammetric determination of trace copper and lead in water - Thành, Nguyễn Mậụ; Hợp, Nguyễn Văn; Luyện, Nguyễn Đình (Hue University Journal of Science: Natural Science, 2019)
The bismuth film electrode prepared in-situ on glassy carbon disk surface (abbreviated to BiFE in-situ) was used as a working electrode for Differential Pulse Anodic Stripping Voltammetry (DP-ASV) for the determination of copper (Cu) and lead (Pb) in an acetate buffer (pH = 5). The influence of the factors on Cu and Pb stripping peak currents (Ip), such as BiIII concentration, pH, deposition potential, deposition time, electrode rotating speed, and interferents, was investigated. At the deposition potential of –1400 mV, the deposition time of 120 s, and other appropriate experimental parameters, the method obtains high sensitivity (0.313 ± 0.004; 0.220 ± 0.010 μA/ppb for Cu and Pb, respectively), good reproducibility of the Ip (RSD = 3.2% and 1.8% (n = 8) for Cu and Pb respectively); low detection limit (3s = 1.8 ppb and 0.8 ppb for Cu and Pb, respectively); linear correlation between Ip and the metal concentration is good in the range of 2.5–25 ppb each metal (R ≥ 0.995). The method has been successfully applied to identify Cu and Pb in three water samples at Thua Thien Hue province.